Ict in the construction sector: Computing the economic benefits - Ruddock, Les (International Journal of Strategic Property Management, 2010)
Any assessment of the extent of the economic benefits for the construction sector from technological change is difficult to determine accurately but in view of the construction sector’s contribution to a nation’s economy, it is important that the impact of technological change on the industry is properly recognised. One area of technological change in the industry — the increased use of information and communication technology (ICT) is considered in this study, which examines the evidence concerning the crucial role of ICT usage and investment in generating growth and improving technical productivity in the industry and considers the question of how the gains from ICT can be evaluated at the industry level. The U.K. construction sector forms the focal point of this study but comparisons are also made with the construction sectors of other industrially developed countries. The results of the analysis find that the construction industry is now beginning to reap the benefits on productivity from the post ‐ 1995 surge in ICT investment. First Published Online: 18 Oct 2010